Channel responses to flooding of Ganga River, Bihar India, 2019 using SAR and optical remote sensing. Issue 4 (15th February 2022) - Khan, Armugha; Govil, Himanshu; Khan, Haris Hasan; Kumar Thakur, Praveen; Yunus, Ali P.; Pani, Padmini
Abstract: Indo Gangetic flood plains are subjected to recurring floods due to large low-lying land areas adjacent to major Himalayan Rivers. Recent floods in the Ganga River during the late withdrawal phase of Indian summer monsoon rains in 2019 had reportedly caused death of ∼200–500 people and damaged major infrastructures in different parts of Bihar state, India. This paper presents a detailed analysis of the spatial extent and temporal pattern of flood inundation areas in Patna district of Bihar using Sentinel-1 Synthetic Aperture Radar (SAR) data. The results obtained using K-means classification show that about 1268 km 2 (20% of the studied portion) of the land area were inundated during the peak flooding conditions on 9th October 2019. The peak flooding lasts for more than 20 days, with a maximum water depth of 18 m in the main river. Owing to the continually changing nature of river morphology by recurring floods, we also analyzed the channel morphology and bar characteristics before, during, and after the floods. Geomorphic change assessment indicates that the total bar occupied area was decreased from 661 km 2 for pre-flood time to 446 km 2 in peak flood time, whereas it retains its original shape in post-flood images.